Study of the pore structure in granite and gabbrodolerite crushed stone grains of various sizes - Elena E. Kameneva; Viktoriya S. Nikiforova (Записки Горного института)
The results of a study on the pore structure of crushed stone grains of various sizes, obtained through staged disintegration of gabbrodolerite and microcline granite – rocks differing in texture, structure, and mineral composition – are presented. Research conducted using X-ray computed microtomography revealed that disintegration leads to changes in the pore structure of the rocks. The increase in overall porosity and pore concentration in the crushed stone grains is associated with the formation of newly developed pores of various sizes and sphericity. A clear relationship between the porosity of the crushed stone grains and their size is absent, which is due to the textural and structural characteristics as well as the mineral composition of the original rocks. The scale factor is evident only in the case of gabbrodolerite, which is characterized by a fine-grained structure, massive texture, and stable mineral composition. Fine gabbrodolerite grains exhibit lower pore concentration compared to larger grains, which aligns with the statistical theory of rock strength, according to which the probability of defects (pores and microcracks) decreases as the sample size diminishes – the smaller the grain size, the higher its strength. In contrast, for porphyritic granites with an uneven grain size, the trend is reversed – smaller grains are more porous. A study of the porosity of individual rock-forming minerals in granite showed that pores are unevenly distributed in the granite crushed stone grains. The highest concentration of pores is typical for microcline. The presence of brittle and porous microcline inclusions in the granite crushed stone grains leads to the formation of new pores and microcracks, whose number increases with the repeated application of load during staged disintegration.